2017
DOI: 10.1097/md.0000000000008878
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable polymer drug-eluting stents versus first-generation durable polymer drug-eluting stents

Abstract: Background:Even if drug-eluting stents (DES) showed beneficial effects in patients with coronary artery diseases (CADs), limitations have been observed with the first-generation durable polymer DES (DP-DES). Recently, biodegradable polymer DES (BP-DES) have been approved to be used as an alternative to DP-DES, with potential benefits. We aimed to systematically compare BP-DES with the first-generation DP-DES using a large number of randomized patients.Methods:Electronic databases were searched for randomized c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…However, this benefit was not realized in the present meta‐analysis, which found no significant difference between BP‐DES and second‐generation DP‐DES for the risk of definite or probable ST at 5 years of follow‐up and on landmark analysis beyond 1 year of follow‐up. Similarly, a meta‐analysis of 13,480 patients showed no significant difference between BP‐DES and first‐generation DP‐DES for the risk of definite or probable ST. Some animal studies demonstrated higher rates of inflammation associated with biodegradable polymers than durable polymers.…”
Section: Discussionmentioning
confidence: 98%
“…However, this benefit was not realized in the present meta‐analysis, which found no significant difference between BP‐DES and second‐generation DP‐DES for the risk of definite or probable ST at 5 years of follow‐up and on landmark analysis beyond 1 year of follow‐up. Similarly, a meta‐analysis of 13,480 patients showed no significant difference between BP‐DES and first‐generation DP‐DES for the risk of definite or probable ST. Some animal studies demonstrated higher rates of inflammation associated with biodegradable polymers than durable polymers.…”
Section: Discussionmentioning
confidence: 98%
“…Different polymers like poly(lactic acid) (PLA), poly( dl ‐lactide) (PDLLA), poly(glycol acid) (PGA), and their copolymers, polylactic‐ co ‐glycolic acid (PLGA), and so on have been used in preparing bioresorbable polymeric stents (Makadia & Siegel, 2011). By the end of the first year of implantation, BP‐DES and the standard‐bearer DP‐DES were proven to be clinically equivalent (Bundhun et al, 2017). Rather, early generation biodegradable polymer DES platforms showed lower rates of stent thrombosis at long‐term follow‐up (Rizas & Mehilli, 2016).…”
Section: Nanotechnology In Different Types Of Stentsmentioning
confidence: 99%
“…Recently, third-generation stents covered with fully biodegradable polymers such as PLGA and PLA have appeared on the market. [ 71 , 72 ]. One example is the everolimus-eluting stent, which consists of a platinum-chromium (Pt-Cr) platform coated with a biodegradable PLGA copolymer.…”
Section: Drug-eluting Stents (Des)mentioning
confidence: 99%